1998
DOI: 10.1172/jci4151
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bacterial products renders macrophages highly susceptible to T-tropic HIV-1.

Abstract: Microbial coinfections variably influence HIV-1 infection through immune activation or direct interaction of microorganisms with HIV-1 or its target cells. In this study, we investigated whether exposure of macrophages to bacterial products impacts the susceptibility of these cells to HIV-1 of different cellular tropisms.We demonstrate that (1) macrophages exposed to bacterial cell wall components such as lipopolysaccharide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 77 publications
1
77
1
Order By: Relevance
“…However, laboratory-adapted X4 HIV-1 strains such as IIIB appear to be blocked during postentry steps in M⌽s (26). Interestingly, exposure to bacterial products renders M⌽s highly susceptible to X4 HIV-1 strains in vitro (27). Similarly, it has been reported that maturation of DCs is associated with up-regulation of CXCR4 expression and a higher susceptibility of DC to infection with X4 HIV-1 strains (28,29).…”
Section: Opposite Effects Of Il-10 On the Ability Of Dendritic Cells mentioning
confidence: 87%
“…However, laboratory-adapted X4 HIV-1 strains such as IIIB appear to be blocked during postentry steps in M⌽s (26). Interestingly, exposure to bacterial products renders M⌽s highly susceptible to X4 HIV-1 strains in vitro (27). Similarly, it has been reported that maturation of DCs is associated with up-regulation of CXCR4 expression and a higher susceptibility of DC to infection with X4 HIV-1 strains (28,29).…”
Section: Opposite Effects Of Il-10 On the Ability Of Dendritic Cells mentioning
confidence: 87%
“…Constructs containing sitespecific mutations were the very generous gift of Professor Hiroyuki Moriuchi, Nagasaki University Graduate School of Biomedical Sciences, Nagasaki, Japan. These constructs contained mutations of the -B1 (Ϫ44), -B2 (Ϫ30), NF-IL-6 (Ϫ92), TRE1/2 (Ϫ345), TRE3/4 (Ϫ327), TRE1/2/3/4, and CD28RE/ B2/ B1 (Ϫ579, Ϫ44, Ϫ30) sites as described previously (27). Constructs had been inserted into the firefly luciferase expression plasmid PGL2-basic.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptional regulation of the CCL5 gene is critical in T lymphocytes (1,2,26,27). The CCL5 promoter contains response elements for the transcriptional activators NF B, AP-1, and NF-IL-6 (26,27) and for late acting factors restricted to T cells (28).…”
mentioning
confidence: 99%
See 2 more Smart Citations